THE COMBINED EFFECTS OF PH AND ACETONITRILE COMPOSITION ON THE SEPARATION OF TWO LINCOSAMIDE ANTIBIOTICS - Vella, Janis; Mifsud, Martina; Bartolo, Nicolette Sammut; Ferrito, Victor; SERRACINO‑INGLOTT, ANTHONY; Azzopardi, Lilian M; Laferla, Godfrey (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Reversed- phase chromatography has become the method of choice to separate compounds which are similar in structure to each other. Selectivity, resolution and retention time can be improved by controlling different variants. The choice of the mobile phase for the analysis is important to achieve the best chromatographic results. The retention time, shape and width of chromatographic peaks are dependent on the buffer pH and also on the amount of organic modifier in the mobile phase. The aim of this study is to separate two lincosamide antibiotics- clindamycin phosphate and lincomycin hydrochloride by using different mobile phases. Each mobile phase was made up of a phosphate buffer and acetonitrile. The mobile phases had different buffer pHs and different percentage compositions of acetonitrile. Analysis was carried out using nine different mobile phases to observe which of them gave the best results in terms of resolution, retention time and peak shape. The best results were given when using a mobile phase having 30% acetonitrile with a buffer pH of 3.0. This work shows the importance of adjusting the amount of the organic modifier in the mobile phase together with the buffer pH. The amount of organic modifier should not be too large as to cause loss of resolution between two neighbouring peaks and not too small so as to result in too long of a retention time. The pH should be chosen to have the greatest percentage of ionised or unionised species of the analyte of interest present.